Liver grafts with major extended donor criteria may expand the organ pool for patients with hepatocellular carcinoma - Lozanovski, Vladimir J.; Khajeh, Elias; Ghamarnejad, Omid; Pfeiffenberger, Jan; Hoffmann, Katrin; Chang, De-Hua; Mieth, Markus; Longerich, Thomas; Strobel, Oliver; Weiss, Karl Heinz; Büchler, Markus W.; Mehrabi, Arianeb (Journal of Clinical Medicine, 2019)
The major extended donor criteria (maEDC; steatosis >40%, age >65 years, and cold ischemia time >14 h) influence graft and patient outcomes after liver transplantation. Despite organ shortages, maEDC organs are often considered unsuitable for transplantation. We investigated the outcomes of maEDC organ liver transplantation in patients with hepatocellular carcinoma (HCC). Two hundred and sixty-four HCC liver transplant patients were eligible for analysis. Risk factor analysis was performed for early allograft dysfunction; primary nonfunction; 30-day and 90-day graft failure; and 30-day, 90-day, and 1-year patient mortality. One-year graft survival was higher in recipients of no-maEDC grafts. One-year patient survival did not differ between the recipients of no-maEDC and maEDC organs. The univariate and multivariate analyses revealed no association between maEDC grafts and one-year patient mortality. Graft survival differed between the recipients of no-maEDC and maEDC organs after correcting for a laboratory model of end-stage liver disease (labMELD) score with a cut-off value of 20, but patient survival did not. Patient survival did not differ between recipients who did and did not meet the Milan criteria and who received grafts with and without maEDC. Instead of being discarded, maEDC grafts may expand the organ pool for patients with HCC without impairing patient survival or recurrence-free survival.